Analysis of the Effectiveness of an Antimicrobial Edible Coating Prepared from Sweet Whey Base to Improve the Physicochemical, Microbiological, and Sensory Attributes of Swiss Cheese - Jayani Siriwardana; Isuru Wijesekara (Advances in Agriculture)
In this research, an edible coating was developed to improve the physicochemical, microbiological, and sensory attributes of Swiss cheese using sweet whey as the main ingredient (84.1%wt/wt). Glycerol (5%wt/wt), sunflower oil (10%wt/wt), guar gum (0.7%wt/wt), and Tween 20 (0.2%wt/wt) were used as other ingredients. Use of sweet whey provided an antibacterial function due to the presence of lactic acid. Delvocid was used as the antifungal agent as it contains 50% of natamycin. In this research, antimicrobial efficiency of three Delvocid concentrations—0.250 g/L (solution 1), 0.275 g/L (solution 2), and 0.300 g/L (solution 3)—was determined. Subsequently, microbial, sensory, and physicochemical properties (hardness, moisture, weight loss, color, pH, fat, and salinity) of the antimicrobial edible solution-coated Swiss cheese obtained at 0, 10, 20, 40, and 60 days of storage at 10°C and 85% relative humidity (RH) were compared with those of commercial paraffin-coated and uncoated Swiss cheeses. Antimicrobial edible solution-coated cheeses exhibited decreased moisture loss, pH change, hardness, color change, salinity change, and fat change. Sensory evaluation tests were carried out by 10 trained panelists using seven-point hedonic scales. Solution 3-coated cheeses obtained the highest acceptability score on 20, 40, and 60 days of storage and exhibited an acceptable and relatively low level of Coliform, yeast, and mold counts throughout the storage. As such, solution 3 was selected as the best Delvocid concentration for coating preparation. Shelf life analysis of antimicrobial edible coating solutions revealed that the shelf life of solutions 2 and 3 extended up to 60 days, while that of solution 1 extended up to 40 days at 8°C and 85% RH. Proximate analysis according to the standard Association of Official Analytical Collaboration (AOAC) procedures revealed that total solid, moisture, protein, fat, total ash, lactose, titratable acidity, and antioxidant activity of the antimicrobial edible coating solution were 25.34% (wt/wt), 74.66% (wt/wt), 8.63% (wt/wt), 11.87% (wt/wt), 0.81% (wt/wt), 3.80% (wt/wt), 0.09% (v/v), and 37.13% (Au/Au), respectively.